Copper-catalyzed transfer methylenation via C(sp3)-C(sp3) bond cleavage of alcohols - Hong, Chuan-Ming; Zhuang, Xin; Luo, Zhen; Xiong, Si-Qi; Liu, Zheng-Qiang; Li, Qing-Lin; Zou, Fei-Fei; Li, Qing-Hua; Liu, Tang-Lin (ORGANIC CHEMISTRY FRONTIERS, 2022)
Transfer hydrogenation between alcohols and carbonyl compounds via C-H bond cleavage is well known, whereas transfer hydrocarbylation remains a challenge due to the cleavage of the unactivated C-C bond. Herein, we disclose a transfer methylenation approach towards various secondary and tertiary alcohols from abundant chemical feedstocks. To the best of our knowledge, this is a de novo report of transfer methylenation via copper-catalyzed beta-carbon elimination to cleave the C(sp(3))-C(sp(3)) bond of tertiary alcohols. This reaction features a broad substrate scope and good functional group tolerance towards sensitive functional groups (carboxylic esters, cyano group, etc.) and can be scaled up, making it an environmentally friendly and step-economical procedure. Meanwhile, the catalytic system exhibits high reactivity (up to 400 TON), and also allows for the late-stage functionalization of a series of bioactive and functional material molecules. Mechanistic studies indicate that the reaction involves a copper-alkoxide-pyridine intermediate.